Kesar Saga: A Critical Perspective of Ladakh - Angmo, Rinchen; Rana, Dr. Meenakshi (South Eastern European Journal of Public Health, 2024)
Ladakh is bounded by rich folklores, folktales, and folk ballads. Out of all the stories, the Kesar saga is the most popular and loved by one and all. All the people of the Ladakh region have grown up listening to the Kesar saga. The epic Kesar has influenced both the Buddhist and the Muslim communities of the region of Ladakh. Though it is the dominating folktale of the region, yet not much research has been done on the subject till date and hence, it needs to be studied properly. In this connection, I am attempting to reimage this heroic tale from the Ladakhi perspective and also to preserve it in the changing times especially when folk narratives are snatched by modern technologies. The attempt is also to make the lesser-known Himalayan regional literature known to a larger audience. Generally, the tradition of storytelling is an important part of Ladakhi culture and tradition, but today due to modern technology like mobile gadgets, television, etc. people are seen drifting away from their traditions keeping themselves busy in their own world of modernism. As a result, today this important practice of oral storytelling is fast vanishing. Therefore, bringing the stories in writing is becoming more urgent than before. So, in the future with technological development; the stories may stay as a source of entertainment and knowledge to the book readers.